Collaborative teaching among ultrasonographers, anesthesiologists, and vascular surgeons: its unique role in specialty training for vascular surgeons in developing countries - Zhang, Peng; Zhang, Mao; Zhang, Qingfeng; Hu, Wei (Frontiers in Medicine, 2024)
This study explored the unique role of collaborative teaching among ultrasonographers, anesthesiologists, and vascular surgeons in the training of vascular surgeons in developing countries. Using qualitative research methods, data were collected through in-depth interviews and observations to analyze the improvement in ultrasound operational skills and basic anesthesia skills among trainees, as well as their satisfaction with collaborative teaching. The results indicate that collaborative teaching significantly enhances trainees’ professional skills and interdisciplinary collaboration abilities, gaining widespread recognition from trainees. This teaching model provides trainees with a comprehensive learning experience through interdisciplinary cooperation, hands-on practice, contributing to the cultivation of vascular surgeons with comprehensive qualities and professional competencies. This study offers new ideas and methods for the training of vascular surgeons in developing countries, holding significant implications for the development of medical education.